Use De Moivre's Theorem to show that if z = cos(q)+isin(q), then (z^n)+(z^-n) = 2cos(nq) and (z^n)-(z^-n)=2isin(nq).

De Moivre's Theorem states that if z = cos(q)+isin(q), then

zn = (cos(q)+isin(q))n = cos(nq)+isin(nq)

But then 

z-n = cos(-nq)+isin(-nq).

Now, cos(-p)=cos(p), as cosine is a symmetric (even) function, and sin(-p)=-sin(p), as sine is an anti-symmetric (odd) fuction. Thus,

z-n  = cos(nq)-isin(nq).

The rest is just algebra:

zn+z-n = [cos(nq)+isin(nq)]+[cos(nq)-isin(nq)] = 2cos(nq).

zn-z-n = [cos(nq)+isin(nq)]-[cos(nq)-isin(nq)] = 2isin(nq).

DA
Answered by Dorian A. Further Mathematics tutor

16099 Views

See similar Further Mathematics A Level tutors

Related Further Mathematics A Level answers

All answers ▸

How do you show that the centre of a group is a subgroup


Find the eigenvalues and eigenvectors of the following 3x3 matrix (reading left to right, top to bottom): (1 0 2 3 1 1 2 0 1)


Prove by induction that, for all integers n >=1 , ∑(from r=1 to n) r(2r−1)(3r−1)=(n/6)(n+1)(9n^2 -n−2). Assume that 9(k+1)^2 -(k+1)-2=9k^2 +17k+6


Understanding differentiation from first principle.


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo

© MyTutorWeb Ltd 2013–2025

Terms & Conditions|Privacy Policy
Cookie Preferences